Predegenerating donor nerve for grafting using focused ultrasound neurotomy - Tak-Ho Chu; Nicolas Lasaleta; Siyun Li; Amanda McConnachie; Leonardo Molina; Saud Alzahrani; Laura Curiel; Samuel Pichardo; Rajiv Midha (Scientific Reports)
Abstract Early experimental evidence suggests that predegenerated nerve graft enhance axonal growth compared to freshly harvested nerve graft in nerve gap repair. However, the practicality of surgically pre-conditioning nerves for grafting remains a major obstacle. Herein, we aim to investigate the feasibility of focal lesioning of nerve tissue using high-intensity focused ultrasound (HIFU) and compare the regenerative effects of predegenerated nerve grafts to freshly harvested grafts in a rat sciatic nerve transection and repair model. As a proof of principle, sciatic nerves were exposed for HIFU lesioning to increase targeting accuracy. HIFU induced focal thermal lesioning to the sciatic nerve, resulting in p75 and cJun up-regulation at the distal segment observed at 7 days post-sonication. All behavioural outcome metrics including von Frey sensory test and walking gait were similar between animals with freshly harvested and predegenerated nerve grafts except soleus muscle weight was significantly higher in the latter group. As well, similar axon histomorphometric results were found in 2-week survival animals. Our findings showed that it is possible to induce Wallerian degeneration in distal nerve for grafting using non-invasive HIFU. However, limited beneficial effects of predegenerated grafts were obtained compared to freshly harvested grafts in nerve gap repair.